Normal Ranges of Right Atrial Strain and Strain Rate by Two-Dimensional Speckle-Tracking Echocardiography: A Systematic Review and Meta-Analysis - Hosseinsabet, Ali; Mahmoudian, Roshanak; Jalali, Arash; Mohseni-Badalabadi, Reza; Davarpasand, Tahereh (Frontiers in Cardiovascular Medicine, 2021)
Background: Normal range values of right atrial (RA) phasic function markers are essential for the identification of normal and abnormal values, comparison with reference values, and the clinical meaning of obtained values. Accordingly, we aimed to define the normal range values of RA phasic function markers obtained by 2D speckle-tracking echocardiography through a meta-analysis and determine the main sources of heterogeneity among reported values. Methods: PUBMED, SCOPUS, and EMBASE databases were searched for the following keywords: “right atrial/right atrium” and “strain/speckle/deformation” and “echocardiography.” Studies were selected that included a human healthy adult group without any cardiovascular diseases or risk factors and that were written in the English language. For the calculation of each marker of RA phasic functions, a random-effect model was used. Meta-regression was employed to define the major sources of variabilities among reported values. Results: Fifteen studies that included 2,469 healthy subjects were selected for analysis. The normal range values for RA strain and strain rate were 42.7% (95% CI, 39.4 to 45.9%) and 2.1 s−1 (95% CI, 2.0 to 2.1 s−1) during the reservoir phase, respectively, 23.6% (95% CI, 20.7 to 26.6%) and −1.9 s−1 (95% CI, −2.2 to −1.7 s−1) during the conduit phase, correspondingly, and 16.1% (95% CI, 13.6 to 18.6%) and −1.8 s−1 (95% CI, −2.0 to −1.5 s−1) during the contraction phase, respectively. The sources of heterogeneity for the normal range of these markers were the number of participants, the type of software, the method of global value calculation, the right ventricular fractional area change, the left ventricular (LV) ejection fraction, the RA volume index, sex, the heart rate, the diastolic blood pressure, the body mass index, and the body surface area. Conclusions: Using 2D speckle-tracking echocardiography, we defined normal values for RA phasic function markers and identified the sources of heterogeneity as demographic, anthropometric, hemodynamic, and echocardiography factors. Systematic Review Registration:https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42021236578, identifier: CRD42021236578.